Regulatory signatures involved in the cell cycle pathway contribute to egg production heterosis in chicken - Jingwei Yuan; Yuanmei Wang; Yanyan Sun; Yunlei Li; Aixin Ni; Qin Li; Hanhan Yang; Xinying Xu; Yunhe Zong; Hui Ma; Jilan Chen (Journal of Animal Science and Biotechnology)
Abstract Background Crossbreeding is widely promoted as an efficient strategy to improve the productivity in agriculture. The molecular mechanism underlying heterosis for egg production is always intriguing in chicken. The transcriptional dynamic changes play a crucial role in the formation of heterosis, but little is known for the egg production traits. Results In present study, we measured the continuous manifestation of heterosis ranging from 2.67% to 10.24% for egg number in the crossbreds generated by reciprocal crossing White Leghorn and Beijing You chicken. The high-quality transcriptomes of ovary for purebreds (WW and YY) and crossbreds (WY and YW) in 5 laying stages were sequenced and integrated to identify regulatory networks relevant to the heterosis. We found highly conserved transcriptional features among 4 genetic groups. By using weighted gene co-expression network analysis (WGCNA), we obtained multiple gene co-expression modules that were significantly correlated with egg number for each group. The common KEGG pathways including apelin signaling pathway, cell cycle, ribosome, spliceosome and oxidative phosphorylation, were screened for the 2 crossbreds. Then, we identified consensus co-expression modules (CMs) that showed divergent expression pattern among crossbred (WY or YW) and purebreds (WW and YY). The hub genes of CMs were again overrepresented in the cell cycle pathway, and the crossbreds exhibited temporally complementary dominance of hub genes in the 5 laying stages. These results suggested that the crossbreds inherited from both parents to maintain the ovary function by cell cycle-related genes, contributing to the persistent heterosis for egg production. Furthermore, the dominant genes including MAD2L1, CHEK2 and E2F1 were demonstrated to function in ovarian follicle development and maturation and could be the candidate genes for egg production heterosis. Conclusion Our study characterized the dynamic profile of genome-wide gene expression in ovary and highlighted the role of dominant expression of cell cycle pathway genes in heterosis. These findings provided new insights for the molecular mechanism of egg production heterosis, which would facilitate the rational choice of suitable parents for producing crossbred chickens with higher egg production.